Youmans neurological surgery - Youmans, Julian R. 1928-; Winn, H. Richard (Elsevier Saunders, 2011)
Helps perform the effective neurosurgical procedures. This title provides details you need to know about functional and restorative neurosurgery/deep brain stimulation, stem cell biology, radiological and nuclear imaging, neuro-oncology, and much more.